2022
DOI: 10.3389/fped.2021.755344
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analyses of Clinical Manifestations and Variant Effects in KCNB1-Related Neurodevelopmental Disorder

Abstract: Objective:Vitro functional analyses of KCNB1 variants have been done to disclose possible pathogenic mechanisms in KCNB1-related neurodevelopmental disorder. “Complete or partial loss of function (LoF),” “dominant-negative (DN) effect” are applied to describe KCNB1 variant's molecular phenotypes. The study here aimed to investigate clinical presentations and variant effects associations in the disorder.Methods: We reported 10 Chinese pediatric patients with KCNB1-related neurodevelopmental disorder here. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Of the 55 distinct missense or loss of function mutations previously described ( de Kovel et al, 2017 ; Bar et al, 2020 ; Xiong et al, 2022 ), 49 of them were located in the S1-S6 transmembrane segments of the protein, 5 were in the C terminus and just 1 of the mutations (a missense mutation, E43G) was located in the N terminus of the channel similar to P17T. Whilst the patient with this E43G mutation did suffer from epileptic seizures they also had a predicted damaging mutation in the GABA A receptor GABRA5 which may underlie many if not all of the clinical symptoms observed ( Bar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 55 distinct missense or loss of function mutations previously described ( de Kovel et al, 2017 ; Bar et al, 2020 ; Xiong et al, 2022 ), 49 of them were located in the S1-S6 transmembrane segments of the protein, 5 were in the C terminus and just 1 of the mutations (a missense mutation, E43G) was located in the N terminus of the channel similar to P17T. Whilst the patient with this E43G mutation did suffer from epileptic seizures they also had a predicted damaging mutation in the GABA A receptor GABRA5 which may underlie many if not all of the clinical symptoms observed ( Bar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a 5 years old boy with neurodevelopmental delay, speech apraxia, normal growth, normal EKG, and normal EEG with no seizures, was found to have a de novo variant in KCNB1 (p.P17T; c49C>A). Proline 17 is located in the N-terminal region of the K V 2.1 channel, proximal to the inactivation domain, which is distinct from all but one of the mutations described above ( de Kovel et al, 2017 ; Bar et al, 2020 ; Xiong et al, 2022 , Figure 1 ). This is a non-conservative amino acid substitution likely to impact secondary protein structure and, as such, is predicted to be a likely pathogenic variant.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In China, Lu et al 31 found a novel de novo KCNB1 variant leading to developmental and epileptic encephalopathy. Xiong et al 32 reported 10 Chinese children with KCNB1 ‐related neurodevelopmental disorders. Nine of those ten patients suffered from epilepsy.…”
Section: Kcnb1 In Epilepsymentioning
confidence: 99%